Determination of Four Cholinomimetics in Edible Fungi and Areca Nut Using Ultra-High Performance Liquid Chromatography Combined With Quadrupole/Time-of-Flight Mass Spectrometry - Junmei Ma; Qiang Li; Yonghuan Yan; Lei Sun; Pin Lv; Yan Zhang (Journal of Food Quality)
Conclusion: The method is sensitive, accurate, and suitable for rapid screening and confirmation of 4 cholinomimetics in edible fungi and areca nut.